2020
DOI: 10.1093/mnras/staa2889
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy and mass assembly: luminosity and stellar mass functions in GAMA groups

Abstract: How do galaxy properties (such as stellar mass, luminosity, star formation rate, and morphology) and their evolution depend on the mass of their host dark matter halo? Using the Galaxy and Mass Assembly (GAMA) group catalogue, we address this question by exploring the dependence on host halo mass of the luminosity function (LF) and stellar mass function (SMF) for grouped galaxies subdivided by colour, morphology and central/satellite. We find that spheroidal galaxies in particular dominate the bright and massi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 101 publications
(176 reference statements)
0
10
0
Order By: Relevance
“…It also provides reliable measurements of absolute magnitudes in a wide wavelength range, stellar masses and SFR. The GAMA survey has been used for various aspects of environmental effects, in particular the impact of group, cluster, local, and large-scale environment on galaxy properties (Wijesinghe et al 2012;Burton et al 2013;Brough et al 2013;McNaught-Roberts et al 2014;Alpaslan et al 2015;Davies et al 2016;Schaefer et al 2017;Grootes et al 2017;Barsanti et al 2018;Wang et al 2018;Davies et al 2019a,b;Schaefer et al 2019;Vázquez-Mata et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It also provides reliable measurements of absolute magnitudes in a wide wavelength range, stellar masses and SFR. The GAMA survey has been used for various aspects of environmental effects, in particular the impact of group, cluster, local, and large-scale environment on galaxy properties (Wijesinghe et al 2012;Burton et al 2013;Brough et al 2013;McNaught-Roberts et al 2014;Alpaslan et al 2015;Davies et al 2016;Schaefer et al 2017;Grootes et al 2017;Barsanti et al 2018;Wang et al 2018;Davies et al 2019a,b;Schaefer et al 2019;Vázquez-Mata et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 7, our integrated satellite counts are very tightly bracketed by the corresponding predicted counts in the TNG100 and TNG300 simulations, where we select satellites at projected distances of < 400 kpc for hosts with M200 = 10 13−14 h −1 M . In addition, we compare to the observed satellite mass function from Yang et al (2008Yang et al ( , 2009, based on a sample of spectroscopically-confirmed satellites in ∼ 300,000 low-z groups (see also Vázquez-Mata et al 2020). Overall, our measured satellite mass function is in remarkably good agreement, especially at low masses (or faint magnitudes).…”
Section: Statistical Background Subtractionmentioning
confidence: 68%
“…the linear ratio between the total r-band flux from a Sérsic profile fit cut at 10 effective radii and the r-band AUTO aperture flux (see also, e.g. Taylor et al 2011;Kelvin et al 2014;Lange et al 2016;Vázquez-Mata et al 2020). The stellar masses are calculated by assuming concordance cosmology with the cosmological parameters being Ω m,0 = 0.3, Ω Λ,0 = 0.7, and h = 0.7 (Taylor et al 2011).…”
Section: Gama Surveymentioning
confidence: 99%